A framework for automatic architectural synthesis in conceptual design phase. (2nd November 2018) - Hartmann, C.; Chenouard, R.; Mermoz, E.; Bernard, A.
ABSTRACT: Architectural synthesis is a key phase of the conceptual design process. In the constant evolution of complex systems, architects have found it difficult to carry out an exhaustive search of all the feasible architectural solutions for a set of given requirements. This paper proposes a computational synthesis framework that automatically generates, from a set of formatted requirements and a sub-systems database, all architectures that are requirement consistent, minimalist regarding the number of components and non-redundant. The resolution principles are based on graph theory representations and Constraint Programming solving techniques. Key features of the framework and an application example are also detailed. Abbreviations: AO: architectural object; BPMN: business process model and notation; CSP: constraint satisfaction problem; DSM: design structure matrix; SE: systems engineering.